Patient outcomes following home-based outpatient parenteral antimicrobial therapy and facility-based outpatient parenteral antimicrobial therapy: a systematic review and meta-analysis - Shinya Hasegawa; Joseph Tholany; Heather Healy; Hiroyuki Suzuki (Cambridge University Press, 2023)
In this systematic literature review and meta-analysis, we did not find a statistically significant difference in readmission and treatment failure rates between home-based and facility-based OPAT. Optimal patient selection for appropriate OPAT location appears to be more important than the location itself for the best OPAT outcome.